THE COMPARATIVE ANALYSIS OF RUSSIAN AND CHINESE LEVEL OF WELFARE - N. Krivorotova; A. Suvorova (Вестник Северо-Кавказского федерального университета, 2022)
This article discusses the need to study the welfare of Russia and China, caused by the changes that have occurred over the past few decades, namely the transformation of the political structure of both states, the change of state regulation methods of social and economic life of citizens, etc. Many Russian andforeign scientists are engaged in the study of this problem, which indicates the relevance of the research topic. The article reveals the meaning of the «standard of living» concept from different points of view, it examines the main statistical indicators directly related to this concept, their dynamics over the past 5-10 years, and also forms the main conclusions characterizing the socio-economic situation of both countries today.